Potential Ekstract Of Red Betel Leaf (Piper crocatum Ruiz & Pav.) as a Natural Hand Sanitizer - Maya Monica Manurung; Tyas Hanurita Subekti; Nanda Dhea Ayu Sawitri; Iin Novita Nurhidayati Mahmuda (Universitas Muhammadiyah Semarang, 2023)
Background: Hands are the most common medium for spreading disease. Red betel leaf has antibacterial bioactive compounds such as flavonoids, alkaloids, polyphenols, tannins, and essential oils. The most common way to clean hands is to use hand sanitizer.Objective: To determine the antibacterial potential of red betel leaf extract (Piper crocatum Ruiz & Pav.) against the growth of Staphylococcus aureus, Streptococcus pyogenes, and Salmonella typhi as an active ingredient in hand sanitizers. Methods: Each bacterium, namely Staphylococus aureus, Streptococcus pyogenes and Salmonella typhi were divided into 6 groups, PEG 5% as a negative control, clindamycin for Staphylococus aureus and Streptococcus pyogenes and chloramphenicol for Salmonella typhi as a positive control, 70% alcohol as a comparison for hand sanitizer, extract 20%, 40%, and 80% as treatment groups. The obstacle zone is measured using a ruler.Results: Zones of inhibition against Staphylococus aureus, Streptococcus pyogenes, and Salmonella typhi were formed at concentrations of 20%, 40%, and 80%. Kruskal Wallis statistical analysis showed significant results with p=0.000.Conclusion: Red betel leaf extract has statistically significant antibacterial activity against Staphylococcus aureus, Streptococcus pyogenes and Salmonella typhi. The extract concentration of 40% is the optimal concentration as a raw material for hand sanitizer.